2004
DOI: 10.1345/aph.1d182
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Problem Classification Systems

Abstract: Finding DRP classifications by computerized search of the biomedical literature with the help of PubMed proved to be difficult. No classification could be found that met all of our criteria for an optimal system. Few classifications have been validated. Three have been tested as to their usability in practice and internal consistency. The Pharmaceutical Care Network Europe system Version 4 comes closest to the defined requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
222
0
17

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(239 citation statements)
references
References 16 publications
0
222
0
17
Order By: Relevance
“…Irrelevante porque é entendido por todos, mas crucial porque nem sempre a compreensão é tão clara como parece. Nos incidentes com medicamentos, outros observam o fato de forma semelhante, quando estudam as conceituações para o termo "drug-related problem" 39 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Irrelevante porque é entendido por todos, mas crucial porque nem sempre a compreensão é tão clara como parece. Nos incidentes com medicamentos, outros observam o fato de forma semelhante, quando estudam as conceituações para o termo "drug-related problem" 39 .…”
Section: Discussionunclassified
“…Assim, em-bora o termo PRM pareça ser auto-explicativo, observam-se diferentes conotações. Em conformidade com a proposta patrocinada pela OMS, a maioria das definições enfatiza a prevenção e inclui os PRMs potenciais, outros analisam somente os PRM reais, outros, ainda, se concentram na perspectiva do paciente ou no resultado da farmacoterapia 39 .…”
Section: Sobre a Terminologia Problema Relacionado A Medicamentosunclassified
See 1 more Smart Citation
“…However, this term or some of its equivalents (Medication Related Problem, Drug-Related Problem) are far from being universally accepted. Some authors have found up to 14 different classifications, some of which have no definition or have not been validated [40][41][42]. On other cases, it has also been used in the context of pharmacovigilance, not only in its definition but as a system for classifying adverse drug reactions [43,44].…”
Section: Construction Of the Knowledge Object (Pcas)mentioning
confidence: 99%
“…), communicative aspects (lack of information, communication, education, etc. ), and only in the case of PCNE explicitly recognize economic problems (the medicine is more expensive than necessary) [32,42].…”
Section: Construction Of the Knowledge Object (Pcas)mentioning
confidence: 99%